Development of Bi-polar plate design of PEM fuel cell using CFD techniques. (5th October 2017) - Wilberforce, Tabbi; El-Hassan, Zaki; Khatib, F.N.; Al Makky, Ahmed; Mooney, Jim; Barouaji, Ahmad; Carton, James G.; Olabi, Abdul-Ghani
Abstract: This paper reviews the common existing designs of flow plates of fuel cells and suggests modifications to some of them to help reduce the pressure drop in the flow channels. Pressure drop is one of the factors that influence the overall performance of the cell both directly and indirectly through interaction with other factors including water management in the cell. The work uses computational fluid dynamics (CFD) to examine different design and study the effect of varying the flow rate (i.e. velocity) on the pressure drop for each of the designs modelled. Again, the designs are optimized by changing different parameters using ANSYS CFX. Results showing the effects of the modifications on pressure drop in the various plates are presented in this paper. From the study of the various designs, a conclusion was drawn that a modification of fuel cell designs in existence using a system similar to the diesel injection system design approach reduced the pressure drop in the fuel cell as shown by the simulation results. This reduction in pressure drop will contribute to the improvement of performance but it must be stressed that other factors also contribute to the overall performance of the cell and reduction in pressure drop alone is not a guarantee of better performance of a certain fuel cell design. Highlights: This work concentrates on pressure drop in PEMFC and suggests ways to reduce it. Review of common PEMFC flow plate designs and their advantages and disadvantages. Several modifications of common designs are suggested and then analysed using CFD. Simulations indicate large pressure drops reductions using the suggested designs. Work seeks to stimulate new designs to accelerate the uptake of the technology.